Internet of Things (IoT) Application in Smart Farming to Optimize Tomato Growth - Dodi Yudo Setyawan; Rahmalia Syahputri; Nurfiana Nurfiana; Nurjoko Nurjoko (Proceeding International Conference on Information Technology and Business, 2022)
Food is a vital need in human life and has become a significant commodity. In this sector, FAO Food and Agriculture Organization predicted in 2050 it will meet the food needs of 9.6 billion people. In addition, the reduction of agricultural land and climate change also contribute to the list of challenges in this sector. These challenges may trigger, for instance, a decline in the volume of agriculture yield, an increase in disease, and shifting cultivation periods. Therefore, it is a concern for all countries whose population growth rates keep increasing, including Indonesia. The fundamental thing in the Indonesian agricultural sector is the need for mass production of agricultural products to improve food security for its 275 million people. We can take advantage of cutting-edge Information and Communication Technology in the form of IoT to manage agricultural land and equip farmers in planning, monitoring, and managing agricultural land. This research aimed to compare the production of tomatoes that plant integrated by the IoT system with convention in a greenhouse situated in Cibodas, Lembang, West Java. The IoT system applied to smart farming uses the Message Queuing Telemetry Transport (MQTT) protocol. We found the productivity of integrated tomatoes increased by about 19% compared to conventional plants. Moreover, the Grade A-B of tomatoes increased by 9,8% while off-grade decreased by 9,6 %. Thus, IoT can optimize the yield of limited plant media.Keyword—Food; Agriculture; IoT; Greenhouse; Tomatoes